Artists' Things : Rediscovering Lost Property from Eighteenth-Century France - Scott, Katie, 1958-; Williams, Hannah, 1980- (Book collections on Project MUSE., 2024)
"This innovative book looks at objects that once belonged to artists, revealing not only the fabric of the eighteenth-century art world in France but also unfamiliar-and sometimes unexpected-insights into the individuals who populated it, including Jean-Antoine Watteau, François Boucher, Jean-Baptiste Greuze, and Elisabeth Vigee-LeBrun"--